Probabilitas Menemukan Elektron Atom Tritium dalam Ruang Momentum dengan Bilangan Kuantum Utama n â‰¤ 3 - Bambang Supriadi; Hildatul Zannah; Salfa Zahroh Ahadah; Aminatus Sa’diah; Erika Divian Chandani (Jurnal Penelitian Pendidikan IPA, 2025)
The tritium atom is an isotope of the hydrogen atom which only has one electron, so this research aims to determine the probability of finding a tritium atom electron ((_1^3)H) in momentum space with the principal quantum number n ≤ 3. This research is included in non-experimental research using literature study methods related to quantum mechanics. To determine the probability data for the electron momentum of the Tritium atom ((_1^3)H) numerical calculations were used using the Matlab R2021a program. The results obtained in this research are in the form of probability values for the electron momentum of the Tritium atom ((_1^3)H) which will provide an overview of the existence of electrons in the momentum space. Based on the research results, it can be shown that in momentum space, the probability of finding a Tritium atom electron increases as the principal quantum number (n) increases.